2021
DOI: 10.3390/ijms22094453
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeted Therapy for the Bone Loss Secondary to Pyogenic Spondylodiscitis Using Medications for Osteoporosis: A Literature Review

Abstract: Pyogenic spondylodiscitis can cause severe osteolytic and destructive lesions in the spine. Elderly or immunocompromised individuals are particularly susceptible to infectious diseases; specifically, infections in the spine can impair the ability of the spine to support the trunk, causing patients to be bedridden, which can also severely affect the physical condition of patients. Although treatments for osteoporosis have been well studied, treatments for bone loss secondary to infection remain to be elucidated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 110 publications
0
4
0
3
Order By: Relevance
“…Recent studies have further suggested an association between osteoporosis and these bone dysfunctions. For example, pyogenic spondylodiscitis is able to cause severe osteolytic and destructive lesions 37 , while osteomyelitis and osteoporosis can both lead to loss of bone mass, where infections can alter RANKL-RANK-OPG signaling that is involved in the regulation of osteoblast and osteoclast behavior 38 . Furthermore, osteoporosis is an oft-occurring bone disease in cholestatic liver diseases, like primary biliary cholangitis and primary sclerosing cholangitis 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have further suggested an association between osteoporosis and these bone dysfunctions. For example, pyogenic spondylodiscitis is able to cause severe osteolytic and destructive lesions 37 , while osteomyelitis and osteoporosis can both lead to loss of bone mass, where infections can alter RANKL-RANK-OPG signaling that is involved in the regulation of osteoblast and osteoclast behavior 38 . Furthermore, osteoporosis is an oft-occurring bone disease in cholestatic liver diseases, like primary biliary cholangitis and primary sclerosing cholangitis 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Los agentes para la osteoporosis comprenden anabolizantes (teriparatida, romosozumab) y antiresortivos (bifosfonatos, denosumab y romosozumab). 2 El denosumab es un anticuerpo monoclonal humano contra el RANKL que inhibe la diferenciación de los precursores de osteoclastos en osteoclastos maduros. Sin embargo, dado que su receptor, RANK, también es expresado por monocitos/macrófagos y células dendríticas, pone de manifiesto la importancia de esta vía en el desarrollo y la maduración del sistema inmune; esto determina que no exista evidencia para la administración del denosumab a pacientes con infección activa, ya que se ha demostrado que podría aumentar las deficiencias del sistema inmune para combatir estos procesos infecciosos; por lo tanto, el denosumab puede empeorar la infección cuando se administra a pacientes con osteomielitis piógena, aunque sea eficaz para la supresión de la osteólisis.…”
Section: Discussionunclassified
“…Sin embargo, dado que su receptor, RANK, también es expresado por monocitos/macrófagos y células dendríticas, pone de manifiesto la importancia de esta vía en el desarrollo y la maduración del sistema inmune; esto determina que no exista evidencia para la administración del denosumab a pacientes con infección activa, ya que se ha demostrado que podría aumentar las deficiencias del sistema inmune para combatir estos procesos infecciosos; por lo tanto, el denosumab puede empeorar la infección cuando se administra a pacientes con osteomielitis piógena, aunque sea eficaz para la supresión de la osteólisis. 2 Asimismo, son necesarios más estudios para aclarar la eficacia del denosumab en el tratamiento de este cuadro infeccioso.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ohnishi T et al [14] experienced a patient case of osteolytic pyogenic spondylodiscitis successfully treated with romosozumab and sensitive antibiotics, which raised the need for an extensive literature review of molecular signaling pathways involved in infection and currently available osteoporosis treatment options against bone defect. Based on accumulating evidence, underlying pathophysiology of bone loss in older patients with pyogenic spondylodiscitis recommends the application of anabolic agents including romosozumab and teriparatide.…”
Section: Pyogenic Spondylodiscitismentioning
confidence: 99%